2021
DOI: 10.3389/fphar.2021.719880
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Wnt/β-Catenin Signaling Pathway as a Potential Therapeutic Strategy in Renal Tubulointerstitial Fibrosis

Abstract: The Wnt/β-catenin signaling pathway plays important roles in embryonic development and tissue homeostasis. Wnt signaling is induced, and β-catenin is activated, associated with the development and progression of renal fibrosis. Wnt/β-catenin controls the expression of various downstream mediators such as snail1, twist, matrix metalloproteinase-7, plasminogen activator inhibitor-1, transient receptor potential canonical 6, and renin-angiotensin system components in epithelial cells, fibroblast, and macrophages.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 178 publications
(178 reference statements)
0
50
0
Order By: Relevance
“…In addition, E-cadherin and vimentin are considered the most important epithelial cell markers and mesenchymal cell phenotypic markers during EMT [ 34 ]. Many experiments have confirmed that the decrease of E-cadherin protein activity is the first step for tumor cells to acquire the ability of dedifferentiation and invasion [ 35 ], that is, E-cadherin protein can inhibit the invasion and migration of tumor cells [ 36 ]. Meanwhile, overexpression of vimentin can promote the invasion and migration of tumor cells [ 37 ], while blocking its expression through molecular biological methods can significantly reduce the invasion ability of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, E-cadherin and vimentin are considered the most important epithelial cell markers and mesenchymal cell phenotypic markers during EMT [ 34 ]. Many experiments have confirmed that the decrease of E-cadherin protein activity is the first step for tumor cells to acquire the ability of dedifferentiation and invasion [ 35 ], that is, E-cadherin protein can inhibit the invasion and migration of tumor cells [ 36 ]. Meanwhile, overexpression of vimentin can promote the invasion and migration of tumor cells [ 37 ], while blocking its expression through molecular biological methods can significantly reduce the invasion ability of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the promoter region of the RAS gene also contains LEF/TCF binding sites, which allows β-catenin to promote the binding of LEF-1 to these sites [ 7 ]. Therefore, targeting the Wnt/β-catenin/RAS signaling pathway could be a potential therapeutic strategy for renal fibrosis [ 8 , 9 ]. In recent years, the replacement therapy of renal fibrosis by natural products has attracted the attention of many scholars [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The expression of E-cadherin protein could be preserved by the genetic ablation of MMP-7 and substantially reduced the expression of total and dephosphorylated β-catenin. Li et al (2021) reviewed that MMP-7 could activate the Wnt/β-catenin signaling pathway after renal injury and urinary MMP-7 may be a noninvasive biomarker of profibrotic signaling in the kidney. In contrast, they discovered that MMP-7 exerts protective effects on the kidney as an adaptive response in cisplatin administration or folic acid-induced AKI animal models.…”
Section: Mmpsmentioning
confidence: 99%